Prostate Cancer: Literature Review - Tonon, Thiarles Cristian Aparecido (2009)
Prostate cancer is characterized by the exaggerated growth of the prostate, with consequent decrease of the caliber and intensity of the urinary jet, being considered one of the main causes of disease and death in the world. Genetic influences, sexual history, exposition to pathogen, industrial chemical, urbanization, diet, hormonal metabolism, besides the age and lifestyle, all are postulated factors in the promotion and disease onset. The diagnostic of this pathology and its stages can be confirmed by: rectal touch, dosage of PSA and phosphatase acid, transrectal ultrasound, biopsy and other methods. If the prostatic tumor be located, it can be appealed to the surgery or radiotherapy, however, if it had expanded to other organs, castration or hormonal blockade are the most appropriate treatments. This review seeks to bring information to professionals, researchers and the general population on the physiopathology, etiology, symptoms, treatment and the prevention of prostate cancer, once its incidence is increasing in the last years.